Diurnal Variation in PDK4 Expression Is Associated With Plasma Free Fatty Acid Availability in People - Yamaguchi, Shintaro (J Clin Endocrinol Metab, 2017)
CONTEXT: Many biological pathways involved in regulating substrate metabolism display rhythmic oscillation patterns. In rodents, clock genes regulate circadian rhythms of metabolic genes and substrate metabolism. However, the interrelationships among substrate metabolism, metabolic genes, and clock genes have not been fully explored in people. OBJECTIVE: We tested the hypothesis that the diurnal expression pattern of pyruvate dehydrogenase kinase 4 (PDK4), a key metabolic enzyme involved in fuel switching between glucose and free fatty acids (FFAs), is associated with plasma FFA concentration and clock genes. DESIGN AND METHODS: We analyzed peripheral blood mononuclear cells (PBMCs), subcutaneous adipose tissue, and plasma samples obtained serially during 24 hours from metabolically healthy women (n = 10) and evaluated the interrelationships among PDK4, plasma FFA, and clock genes. We also determined the potential mechanisms responsible for PDK4 transcriptional regulation by using primary human PBMCs and adipocytes. RESULTS: We found that PDK4 diurnal expression patterns were similar in PBMCs and adipose tissue (ρ = 0.84, P < 0.001). The diurnal variation in PBMC PDK4 expression correlated more strongly with plasma FFA and insulin (ρ = 0.86 and 0.63, respectively, both P < 0.001) concentrations than clock genes. Data obtained from primary culture experiments demonstrated that FFAs directly induced PDK4 gene expression, at least in part through activation of peroxisome proliferator-activated receptor α. CONCLUSIONS: Our results suggest that plasma FFA availability is an important regulator of diurnal expression patterns of PDK4, and we identify a novel interaction between plasma FFA and cellular diurnal rhythms in regulating substrate metabolism.